Optical Biomedical Diagnostics: Sensors with Optical Response Based on Two-Photon Excited Luminescent Dyes for Biomolecules Detection. (15th May 2008) - Yashchuk, V. M.; Yarmoluk, S. M.; Kudrya, V. Yu.; Losytskyy, M. Yu.; Tokar, V. P.; Kravchenko, V. M.; Kovalska, V. B.; Balanda, A. O.; Kryvorotenko, D. V.
Abstract : The spectral properties of novel styryl dyes developed for the biomacromolecules (such as DNA) detection and imaging were investigated. The energy structures of dye molecules were examined. The spectral data prove that dyes aggregate and interact with DNA. The essential increase of the fluorescence intensity of dyes in the presence of DNA was observed. The photostability and phototoxic influence on the DNA of several styryl dyes were studied by analyzing absorption, fluorescence, and phosphorescence spectra of these dyes and dye-DNA systems. Changes of the optical density value of dye-DNA solutions caused by the irradiation were fixed in the DNA and dye absorption wavelength regions. Fluorescence emission of dye-DNA complexes upon two-photon excitation at wavelength 1064 nm with the 20-nanosecond pulsed YAG:Nd 3 + laser and at 840 nm with the 90 famtosecond pulsed Ti:sapphire laser was registered. The values of two-photon absorption cross-sections of dye-DNA complexes were evaluated.